Impact of AI Automation on Job Security - Nadiradze, Mari; Kučera, Dušan; Viktora, Martin; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Rapid integration of AI in the current economy represents one of the most profound technological disruptions of the 21st century, with implications that surpass previous historical technological advancements such as Industrial or Digital Revolution. Despite offering immense opportunities in terms of automation which can increase efficiency of businesses and stimulate economic growth, its potential effects on the labor market through AI induced job displacements threatens job security of many employees. This study investigates the duality of AI’s market growth, with a focus on occupational exposure, task vulnerability, educational disproportionation and cognitive skill requirements. Findings reveal that AI market growth outpaces traditional economic benchmarks, with middle and high skill professionals with higher education being disproportionately exposed to AI automation. The study further considers specific cognitive abilities and tasks that form core aspects of positions that are exposed to AI automation. Assessment of challenges and opportunities presented by AI are discussed, as well as ethical considerations that have to be accounted for in order to assure a smooth transition for businesses and the labor market to adapt.
Vedoucí práce: Dušan Kučera
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses